An accurate model of high-performance manufacturing spiral bevel and hypoid gears based on machine setting modification. (October 2016) - Ding, Han; Tang, Jinyuan; Zhong, Jue
Highlights: An accurate model of machine setting modification considering the residual ease-off. Machine setting modification considering the tooth flank geometric and physical properties. A trust region algorithm with control strategies is employed to obtain the accurate solutions. A closed-loop measurement-modification-manufacturing (3M) model is established for the high-performance manufacture. Abstract: Machine setting modification especially considering the tooth contact performance is always vital to design and manufacture for the spiral bevel and hypoid gears. With the application of new manufacture concepts and advanced design methods, a closed-loop complex model is established to execute the high-performance manufacture. Firstly, an optimization model of machine settings modification considering the residual ease-off is established by correlating the tooth flank represented by universal machine settings. Furthermore, a trust region algorithm with control strategies concerning: (i) double Dogleg algorithm for the iteration step and (ii) updating damping efficient for the trust region radius is employed to obtain the target flank. Finally, a closed-loop measurement-modification-manufacturing (3M) model for high-performance manufacture of the spiral bevel and hypoid gear is established. Where, it mainly describes the accurate machine setting modification considering tooth contact performances. Some numerical examples in practical application can verify the accuracy and performance of the proposed model.